Moebius sequence and the oral health condition: Case report (Research, Society and Development, 2021)
Moebius Syndrome is a rare congenital neurological disorder, with a prevalence of 1:250,000 individuals, with no defined etiology. The main feature of the syndrome is facial nerve palsy (VII pair of cranial nerve), which can compromise other nerves, the diagnosis can be made in childhood. Treatment must be carried out by a multidisciplinary team with periodic monitoring. The objective of this work was to report the case of a patient affected by Moebius Syndrome, emphasizing the oral health condition. This work was carried out at the Center for Attention and Research in Craniofacial Anomalies - CEAPAC located in the city of Cascavel-PR. Patient M.C.S.R. nineteen years old, female, was referred to CEAPAC for dental treatment. On physical examination, typical characteristics of patients with Moebius Syndrome were observed, and the intraoral examination revealed a precarious condition of the teeth and adjacent tissues. Dental treatment was performed in a clinical setting and under local anesthesia. Considering the serious implications triggered by the syndrome, early and periodic monitoring of the patient by a multidisciplinary team is extremely important.